+0  
 
0
85
1
avatar

(2×10^4) (3×10^7) =

Guest Sep 18, 2017
Sort: 

1+0 Answers

 #1
avatar+79735 
+1

(2×10^4) (3×10^7)

 

We can rearrange this as

 

( 2 x 3) ( 10^4 x 10^7)  =

 

( 6) [ 10^ (4 + 7) ] =

 

6 x 10^11  =

 

600,000,000,000 

 

 

cool cool cool

CPhill  Sep 18, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details